TECHNOLOGY FOR DEVELOPING COMMUNICATIVE COMPETENCE OF STUDENTS IN HIGHER TECHNICAL EDUCATION FIELDS (IN THE EXAMPLE OF ENGLISH LANGUAGE) - Nazarov, Rustam (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article provides a lot of information about the technology for developing students' communicative competence in higher technical education (in the example of English). It is considered that the development of technology should be carried out through foreign experiences.